THYROID FUNCTION ABNORMALITIES IN PATIENTS WITH CHOLELITHIASIS: A HOSPITAL-BASED CROSS-SECTIONAL STUDY - SAXENA, AVANISH KUMAR; FATIMA, ANAM; VENKATA SIVA, KUNDRAPU VEERA; PARIYA, ANUSHKA; CHINMAYI, VAYALAPALLI SYAMA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to analyze the association between thyroid function abnormalities and cholelithiasis, focusing on the prevalence and types of thyroid dysfunctions in patients with gallstone disease compared to a healthy control group. Methods: A comparative, hospital-based cross-sectional study was conducted in the department of general surgery at a tertiary care medical college. The study included 60 patients diagnosed with cholelithiasis (Group A) and 60 age-matched healthy individuals (Group B). Detailed history, physical examinations, ultrasound imaging, and thyroid function tests (TFTs) were performed. TFTs included measurements of free triiodothyronine (FT3), free thyroxine (FT4), and thyroid-stimulating hormone. Patients were categorized based on thyroid status into euthyroid, subclinical and clinical hypothyroidism, and hyperthyroidism. Statistical analysis was performed using SPSS version 21.0, with significance set at p<0.05. Results: The study revealed a female preponderance in cholelithiasis cases (76.67% in Group A vs. 65.00% in Group B). The mean age and BMI were comparable between the groups. Thyroid function abnormalities were more prevalent in the cholelithiasis group (p=0.0251), with a higher incidence of hypothyroidism compared to the control group. Subclinical hypothyroidism was the most common thyroid dysfunction in cholelithiasis patients. Common complaints in the cholelithiasis group included anemia, menstrual irregularities, skin changes, and weakness. Conclusion: The study demonstrates a significant association between cholelithiasis and thyroid function abnormalities, particularly hypothyroidism. The findings suggest the need for routine thyroid function evaluation in patients with cholelithiasis, which could influence management strategies and improve patient outcomes.